Impaired Lung Function Due to Occupation by Exposure to Particulate Matter 2.5m (PM2.5) in Fish Smokers (International Journal of Scientific Research and Management (IJSRM), 2023)
Backgrounds: As a coastal City, Ternate has smoked fish products that are traditionally managed by burning using firewood or coconut shells, resulting in air pollution pollutants, like fine particulate matter (PM2.5), an air pollutants which are harmful to the health of fish smoking workers, such as pulmonary function impairment. Purpose: This study aims to determine the effect of PM2.5 exposure on lung function impairment of fish smoking workers in Ternate City. Method: It was a cross-sectional study design, purposive sampling technique of 15 people from a total of 12 smoking houses. Result: The median of PM2.5 concentration in fish smoking houses was 440.15mg/m3 and about 86% of workers had been exposed to PM2.5 exceeded the nationally required daily quality standard, 53.3% of respondents had lung function impairment based on FEV1/FVC lung capacity measurements, from the statistical analysis results obtained p = 1, meaning that there was no difference pulmonary function impairment in workers with PM2.5 exposure that exceeds the quality standard and does not exceed the quality standard. OR 1.167 was obtained, meaning that workers exposed to PM2.5 > quality standards have odds 1.167 times higher to have lung function impairment than workers exposed to PM2.5 ≤ quality standards. Conclusion: Exposure to PM2.5 that exceeds the quality standard will increase the risk of having lung function impairment in fish smoking workers in Ternate City.